Analysis Students’ Motivation in Extensive Reading at English Education Study Program Muhammadiyah University of Bengkulu: At English Education Study Program Muhammadiyah University of Bengkulu - Muhammad Ja’far Shodiq; Fetriani (Teaching English and Language Learning English Journal, 2026)
This study aims to analyze students’ motivation in extensive reading, focusing on the motivational aspects that influence students in engaging with extensive reading activities in the English Education Study Program of the University of Muhammadiyah Bengkulu, and to identify the most dominant aspect. The background of this research lies in the importance of extensive reading for improving grammar, reading fluency, and text comprehension, while students’ engagement in this activity remains varied. A descriptive qualitative method was employed, using 20 closed-ended and one open-ended questionnaire items based on a Likert scale as the instrument, involving 15 sixth-semester students as respondents. The data were analyzed by calculating the percentage scores of five motivational aspects: curiosity and autonomy, enjoyment and interest, academic benefits, teacher and peer influence, and self-efficacy. The analysis revealed that students’ motivation in extensive reading was high, with all motivational aspects falling into the “high” category. Curiosity emerged as the most dominant aspect (85.3%), followed by academic benefits (84.6%), interest (83.3%), teacher and peer influence (81.3%), and self-efficacy (80.6%). These findings indicate that internal factors—particularly curiosity and autonomy—are the main drivers of students’ engagement in extensive reading. It is therefore recommended that educators provide students with the freedom to choose reading materials and create a learning environment that fosters curiosity. Keywords: Motivation, Extensive Reading, Curiosity.